Physicochemical and Sensory Properties of Broiler Chicken Breast Meat Stored Frozen and Thawed Using Various Methods - Anna Augustyńska-Prejsnar; Małgorzata Ormian; Zofia Sokołowicz (Journal of Food Quality)
The paper presents an analysis of the impact of freezing storage duration (1, 3, 5, and 7 months) and thawing methods, namely, in atmospheric air, water, and using microwave oven on the quality properties of broiler chicken breast meat. The physicochemical indicators of raw breast meat after thawing and after being subjected to heat treatment were evaluated. The sensory evaluation was also conducted. The findings indicate that the duration of storage has effects on the quality of meat stored frozen at −20°C. Unfavourable changes (p<0.05) were observed between the first and seventh months of freezing storage in respect of such areas as increased drip loss, increased thermal loss, colour changes, and reduced ash content in thawed breast meat as well as in those subjected to heat treatment. Unfavourable changes in the sensory properties, namely, diminished intensity of flavour and aroma, were also observed. The analysis revealed significant (p<0.05) impacts of thawing methods on the meat’s quality properties, depending on the duration of freezing storage. The application of microwave oven method of thawing meat enabled the retention of better physicochemical properties (reduction of drip and thermal losses and increased ash content) as well as sensory properties such as the desirability of the flavor and juiciness of meat stored for one-month period. A longer period of freezing storage (5 and 7 months) revealed higher degrees of colour saturation towards red (a∗) in raw breast meat as well as reduced brittleness of breast meat thawed using microwave oven method prior to and after the heat treatment in comparison to those thawed using atmospheric air and water. Practical Applications. The duration of freezing storage and thawing methods has impacts on the meat’s quality, including its processing value. The current study has its practical implications due to the immense consumption of broiler chicken meat, the high proportion of deep frozen meat products in commerce, and the acceptability and popularity of frozen stored meat in households. The current study enables one to ascertain how the physicochemical and sensory properties of broiler chicken breast meat change over the period of freezing storage (for 1, 3, 5, and 7 months) and which of the applied thawing methods (in atmospheric air, water, or microwave method) is most favourable for retaining meat’s best quality.